Designing Knowledge Map for Knowledge Management projects Using Network Analysis - heidar najafi; mohammad aghdasi; Babak Teimurpoor (Journal of Information Technology Management)
In this research knowledge management has been studied as an interdisciplinary area. We aim to find an answer for this question that "what are the scientific structure and knowledge map of knowledge management projects regarding these two aspect of subject areas and keywords. For this purpose, nearly 40000 scientific documents including knowledge management as one of their keywords were selected from Scopus database and were studied in various subject areas. In this research,bar charts have been drawn for each index of subject areas and keywords. Besides, using Co-occurrence matrix, adjacency graphs were drawn and then clustered using Average-Link algorithm. Bar charts and graphs were drawn using R and Excel software. The results of this research showed that among the researches on knowledge management in the world, the most relevant scientific fields to knowledge management are Computer Sciences with 32.5%, Business, Management and Accounting with 14.5%, Engineering with 13.7%, Decisive Sciences with 12.6%, Mathematics with 7.07%, and Social Sciences with 6.63%, respectively. The most keywords collocate with knowledge management in the world are Human-Computer Interaction, Information Management, Systems Management, Information Technology, Manufacturing, Acquisition of Knowledge, Semantics, Knowledge Transfer, Ontology and Information Retrieval.